Prosedur Pembiayaan pada Bank Sumut Syariah dari Analisis Kelayakan hingga Monitoring - Abidzar Fikri Simamora; Ananda Fitriani Oktavia; Putri Chairunnisa Pane (Academic Solution Publisher, 2025)
This study aims to evaluate the financing methods at PT Bank Sumut Sharia Business Unit, from feasibility analysis to financing monitoring. The approach used in this study is descriptive qualitative by collecting data through interviews, observations, and document studies. The findings of the study indicate that the bank has implemented the principle of prudence through 5C analysis and a rating system to assess customer eligibility. However, the character aspect of customers remains a major weakness due to the potential moral hazard that may arise after financing is disbursed. In the implementation stage of the contract, most financing is based on the murabahah contract including murabahah bil wakalah, but there is a lack of customer understanding regarding the contract, which can increase sharia risk. Financing monitoring is carried out through field supervision and persuasive handling of problematic financing and restructuring, but it is more curative in nature. Therefore, it is important to improve character analysis, education about contracts, and more preventive monitoring.